2009
DOI: 10.1089/jmf.2008.0005
|View full text |Cite
|
Sign up to set email alerts
|

Orthosiphon stamineus Leaf Extract Protects Against Ethanol-Induced Gastropathy in Rats

Abstract: Orthosiphon stamineus Benth., which is used as a gastroprotective herbal remedy in Malaysia, was assessed for its anti-ulcerogenic activity against ethanol-induced ulcers in rats. Fifty percent methanol was used to extract the oven-dried O. stamineus leaves. The extract was then lyophilized with a rotary evaporator and freeze-dried. Oral administration of O. stamineus methanolic extract (OSME) (125, 250, 500, and 1,000 mg/kg) was found to significantly decrease the ulcer index (P < .01, P < .001, P < .001, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…The recommended daily dose in folk medicine is at least 6-10 times lower than the highest daily dose tested in mice in this study (i.e., 500-4000 mg/kg body weight po). It is of note that these doses were comparable to or higher than those reported to induce pharmacological effects in rodents such as anti-ulcer effects in rats (125-1000 mg/kg body weight) (Yam et al, 2009), diuretic effects in rats (5-10 mg/kg body weight po) (Adam et al, 2009), and anti-inflammatory and analgesic effects in rats and mice (500-1000 mg/kg body weight po) (Yam et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The recommended daily dose in folk medicine is at least 6-10 times lower than the highest daily dose tested in mice in this study (i.e., 500-4000 mg/kg body weight po). It is of note that these doses were comparable to or higher than those reported to induce pharmacological effects in rodents such as anti-ulcer effects in rats (125-1000 mg/kg body weight) (Yam et al, 2009), diuretic effects in rats (5-10 mg/kg body weight po) (Adam et al, 2009), and anti-inflammatory and analgesic effects in rats and mice (500-1000 mg/kg body weight po) (Yam et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
“…In Sprague-Dawley rats, an acute oral toxicity study found no mortality and no overt toxicity up to the highest dose of Orthosiphon stamineus extract tested (LD 50 > 5000 mg/kg body weight po) (Abdullah et al, 2009), while a 14-day repeated dose study found no deaths and no other adverse effects on females treated orally with doses of Orthosiphon stamineus extract ranging from 500 up to 5000 mg/kg body weight/day (Chin et al, 2008). In addition, pharmacological studies of Orthosiphon stamineus extracts have not revealed any adverse effect on rats and mice either (Adam et al, 2009;Beaux et al, 1999;Yam et al, 2008Yam et al, , 2009. Considering the lack of overt toxicity in the aforementioned rodent studies and in a preliminary experiment with Swiss Webster mice, 4000 mg/kg of body weight/day (for 3 days) was set as the upper limit of the dose range tested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, O. stamineus leaf extract is widely used as an herbal remedy for kidney and urinary tract disorders. Previous studies revealed the anti-oxidant [51,52], anti-apoptotic [51], hepatoprotective [52] and gastroprotective [53] properties and also identified the major active fractions include eupatorin, sinensetin, 3′-hydroxy-5, 6, 7,4′-tetramethoxyflavone [54] and rosmarinic acid [55]. N. fruticans and O. stamineus extracts enabled the host to survive both antibiotic-sensitive and antibiotic-resistant S. aureus infection without interfering with bacterial viability, suggesting that these extracts possess compounds capable of targeting the host defense mechanism or attenuating bacterial virulence traits.…”
Section: Discussionmentioning
confidence: 99%
“…effects against alcohol-induced gastropathy, liver damage, pyrexia (Yam et al, 2007(Yam et al, , 2009a(Yam et al, , 2009b, anti-inflammatory and analgesic effects (Yam et al, 2008). Studies on the antimicrobial activity of O. stamineus have been reported against Staphylococcus aureus, Streptococcus agalactiae and Vibrio parahemolyticus (Ho et al, 2010;Mohammed et al, 2012).…”
Section: Introductionmentioning
confidence: 99%